2010
DOI: 10.1021/bc1001196
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytokine Secretion from Primary Macrophages due to Dectin-1 Mediated Uptake of CpG DNA/β-1,3-Glucan Complex

Abstract: Unmethylated CpG sequences (CpG DNA) can induce Th1 response and thus become a potential immunotherapeutic agent. A key step in the treatment is to transport CpG DNA to its receptor TLR9 located in the endocytosis pathway of target immune cells. For the effective transport, we prepared a novel complex from a β-1,3-glucan schizophyllan (SPG) and CpG DNA, and administered the complex to murine peritoneal macrophages that had been previously activated by thioglycollate and expressed a major β-1,3-glucan receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Anionic β‐1,3‐glucan ⋅4 complex showed higher intercellular uptake and photoinduced cytotoxicity toward RAW264.7 cells than that of the neutral β‐1,3‐glucan ⋅1 and β‐1,3‐glucan ⋅3 complexes. This result is consistent with the intracellular macrophage uptake of anionic β‐glucan ⋅ DNA complexes and anionic β‐glucan derivatives, such as glucan phosphate and carboxymethyl pachyman, which was much higher than that of native β‐glucans . However, the receptor has not yet been decided.…”
Section: Photoinduced Cytotoxicity Of Fullerenes Incorporated Into Sosupporting
confidence: 55%
See 1 more Smart Citation
“…Anionic β‐1,3‐glucan ⋅4 complex showed higher intercellular uptake and photoinduced cytotoxicity toward RAW264.7 cells than that of the neutral β‐1,3‐glucan ⋅1 and β‐1,3‐glucan ⋅3 complexes. This result is consistent with the intracellular macrophage uptake of anionic β‐glucan ⋅ DNA complexes and anionic β‐glucan derivatives, such as glucan phosphate and carboxymethyl pachyman, which was much higher than that of native β‐glucans . However, the receptor has not yet been decided.…”
Section: Photoinduced Cytotoxicity Of Fullerenes Incorporated Into Sosupporting
confidence: 55%
“…Anionic b-1,3-glucan·4 complex showed higheri ntercellular uptake and photoinduced cytotoxicity toward RAW264.7 cells than that of the neutral b-1,3-glucan·1 and b-1,3-glucan·3 complexes.T his result is consistentwith the intracellular macrophage uptake of anionic b-glucan·DNA complexes and anionic b-glucan derivatives,s uch as glucan phosphate and carboxymethyl pachyman, which was much highert han that of native b-glucans. [103][104][105] However,t he receptor has not yetb een decided.I nc ontrast, none of the b-1,3-glucan·C 60 derivative complexes exhibited photoinduced cytotoxicity towardH eLa cells ( Figure 6B). Consequently,t he photoinducedc ytotoxicity of the b-1,3-glucan·4 complex had ah ighers electivity for RAW264.7 cells than that of HeLa cells.…”
Section: Photoinduced Cytotoxicities Of CDX and Polysaccharide· Fullementioning
confidence: 64%
“…To make a complex between CpG ODNs and schizophyllan (SPG), CpG ODNs need additional sequences of phosphorothioate backbone of 40-mer polydeoxyadenylic acid (dA 40 ) at the 5′ or 3′ end (20,22). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although we previously demonstrated that mouse and humanized CpG ODN with PO poly(dA) at the 5′ end complexed with SPG enhanced cytokine production and acted as an influenza vaccine adjuvant (20,21), it has been difficult to achieve high yields of the CpG-SPG complex toward its more efficient and cost-effective preclinical as well as clinical development. Recently, when the PS backbone of the dA sequence was linked to CpG ODN, the efficacy of complex formation was elevated by nearly 100% (22). However, a thorough investigation has yet to be conducted to identify the best humanized CpG sequence and optimization of factors to gain all-in-one activities of the four types of CpG ODN.…”
mentioning
confidence: 99%
“…SPG has several advantages. The SPG used in this study was medical grade [13] and was up taken in macrophages and dendritic cells (DCs) via phagocytosis [14]. Furthermore, previous studies showed that Dectin-1, which was known to be the receptor of SPG, had a key role in the phagocytosis of SPG in macrophages [15,16].…”
Section: Introductionmentioning
confidence: 99%